Local wisdom as legal dispute settlement: how Indonesia’s communities acknowledge Alternative Dispute Resolution? - Didik Sukriono; Sudirman Sudirman; Desinta Dwi Rapita; A. Rosyid Al Atok; Alfan Bramantya (Faculty of Law, University of Muhammadiyah Malang, 2025)
This paper examines the evolution of legal dispute resolution mechanisms within non-litigation channels, focusing on the traditional villages of Blitar and Karangasem in Indonesia from 1984 to 2023. There is a need to understand how local wisdom contributes to effective dispute resolution, particularly in regions where formal legal institutions may be limited. This research analyses how indigenous communities integrate Alternative Dispute Resolution (ADR) principles with customary (adat) law, fostering a hybrid system that balances cultural values and contemporary legal frameworks. The paper draws on ethnographic fieldwork, in-depth interviews with traditional leaders, and case studies of dispute settlements in the selected villages. Historical records and legal documents regarding customary disputer solutions were also examined. The results indicate that the villagers have modified their traditional approaches over the last four decades to deal with contemporary problems such as land disputes, family conflicts, and governance issues. This study also focuses on consensus, reconciliation, and restorative justice, which are considered key factors for social cohesion and dealing with social conflicts. The findings highlight that integrating ADR with adat-based mechanisms strengthens legal pluralism and provides an alternative resolution of issues; this integration is more appropriate than litigation in rural, culturally diverse societies. Moreover, the study suggests that these non-litigation practices are socially cohesive between community members because they ensure that dispute resolution is aligned with the community’s cultural norms and common identity. The study also theorizes that justice and social order can be maintained through a better understanding and empowerment of customary laws. This research provides insight into the wider world of legal pluralism as it explores how traditional modes of dispute resolution remain important within modern legal systems.